Combining effect of camellia oil and squalene on hyperlipidemia-induced reproductive damage in male rats - Xu, Qi; Luo, Minhui; Cheng, Gengjinsheng; Zhong, Qi; Guo, Yixing; Luo, Jianghong (Frontiers in Nutrition, 2022)
Camellia oil (CO), a common edible oil in China, contains a variety of active ingredients. In this study, we explored the combining effect and optimal feeding time of CO and squalene on hyperlipemia-induced reproductive damage rats and probably provided supportive data for use of CO for health benefits. We established the hyperlipidaemia-induced reproductive damage model, and then the successfully modeled rats were randomly classified into four groups including a model control (MC) group, a camellia oil (CO) group, a camellia oil + squalene (COS) group, and a sildenafil (SN) group, which were feeding with different subjects during days 30 and 60. The normal (NC) group was fed under the same conditions. Results showed that compared with the MC group, the CO, COS, and SN groups could significantly decline the serum TG, TC and LDL-C levels, increase the serum testosterone levels, the sperm counts in epididymidis and organ coefficients of penises, and no pathological change in penis and testis at days 30 and 60. Compared with the pure CO, the mixture of CO and squalene could significantly enhance the effect of decreasing the concentrations of TG, TC, and LDL-C and increasing the serum testosterone level and sperm count of epididymal tail, and the results of day 30 were better than those of day 60. Thus, CO and squalene have a combining effect on lowering blood lipid and promoting the recovery of erectile and sexual function on hyperlipidemia-induced reproductive damage rats on day 30.